Expert-derived monitoring thresholds for impacts of megaherbivores on vegetation cover in a protected area. (15th July 2016) - Smit, Izak P.J.; Landman, Marietjie; Cowling, Richard M.; Gaylard, Angela
Abstract: Monitoring is meant to inform conservation authorities, yet managers often don't know when to respond to monitoring results. One of the reasons is that management often lacks consensus on monitoring thresholds for intervention. This results in aimless monitoring without a clear directive on when monitoring indicates a trajectory towards an unacceptable state or impending change, which possibly necessitates intervention. Although experts rarely provide simple, measureable and quantifiable monitoring thresholds as required by management, they are often more comfortable expressing opinions on whether a specific area is desirable or not. This allows thresholds to be reverse engineered : by getting experts to identify sites as desirable and undesirable, field variables can subsequently be measured to derive the boundary between subjectively identified desirable and undesirable states. Such a boundary provides a defendable point for management to assess and consider intervention. Here we describe the identification of monitoring thresholds by defining the limits of desirable canopy cover, derived from expert stakeholder preferences, in the Sundays Spekboom Thicket vegetation of the Addo Elephant National Park, South Africa. The park has experienced variable utilization intensity by large herbivores, especially elephant. For years managers have grappled with the question of what percentage shrub canopy cover is desirable as a management target, but science has failed to provide this. Using experts to assess pre-selected sites as desirable or undesirable across a range of canopy covers, we showed that a canopy cover of ∼65% (±15%) would be desirable for expert stakeholders. We then used satellite imagery to map canopy cover, providing managers for the first time with a large-scale map of canopy cover, indicating desirability status. This approach was useful for facilitating joint-decision making between conservation agencies and stakeholders on tangible indicators of achieving goals, and may be useful in fostering relationships, trust, mutual understanding and transparency, characteristics critical for managing complex socio-ecological systems. Highlights: Monitoring often fails to inform if thresholds for intervention are lacking. However, it is hard to define these monitoring thresholds. Here we introduce an approach to reverse engineer thresholds from expert opinion. Experts rate sites as desirable or not, and then boundary conditions are measured. Boundary between desirable and undesirable sites are practical monitoring thresholds.